2012
DOI: 10.1001/archinternmed.2012.945
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With False-Positive ST-Segment Elevation Myocardial Infarction Diagnoses at Primary Percutaneous Coronary Intervention–Capable Centers

Abstract: More than a third of patients referred for primary PCI from the emergency department did not have a STEMI. Multiple patient-level characteristics were significantly associated with an increased odds of false-positive STEMI activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 30 publications
4
80
3
Order By: Relevance
“…9,11,22 Second, the presence of equivocal ECG findings (such as presumed new left bundle branch block or isolated posterior MI) was the strongest factor limiting direct cath lab transfer in our multivariable model. The United States health system tolerates a certain degree of false activation of the cath lab for suspected STEMI patients 23,24 ; this threshold may need to CI indicates confidence interval; cath, catheterization; ED, emergency department; and OR, odds ratio. *Odds of the outcome in patients directly transferred to the cath laboratory versus patients transferred to an ED/ward.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,22 Second, the presence of equivocal ECG findings (such as presumed new left bundle branch block or isolated posterior MI) was the strongest factor limiting direct cath lab transfer in our multivariable model. The United States health system tolerates a certain degree of false activation of the cath lab for suspected STEMI patients 23,24 ; this threshold may need to CI indicates confidence interval; cath, catheterization; ED, emergency department; and OR, odds ratio. *Odds of the outcome in patients directly transferred to the cath laboratory versus patients transferred to an ED/ward.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, only one study I am aware of has addressed the problem of false positive activations appropriately [19]. In this study, a true positive required a flow grade less than thrombolysis in myocardial infarction (TIMI) grade 3 flow in at least one artery, and found that 36 % of cases were false positive activations.…”
Section: Pseudoinfarction Missed Stemi and Appropriate Cath Lab Actmentioning
confidence: 93%
“…10 For example, acute ST-elevation MI (STEMI) registry studies have labeled patients presenting with acute ST elevation and nonobstructive CAD on angiography as a "false-positive STEMI diagnosis". 10, 11 In some cases this may be appropriate if the ECG is misinterpreted.…”
Section: Clinical Recognitionmentioning
confidence: 99%